Major histocompatibility complex peptide ligands as olfactory cues in human body odour assessment - Milinski, Manfred (The Royal Society, 2013)
In many animal species, social communication and mate choice are influenced by cues encoded by the major histocompatibility complex (MHC). The mechanism by which the MHC influences sexual selection is a matter of intense debate. In mice, peptide ligands of MHC molecules activate subsets of vomeronasal and olfactory sensory neurons and influence social memory formation; in sticklebacks, such peptides predictably modify the outcome of mate choice. Here, we examine whether this evolutionarily conserved mechanism of interindividual communication extends to humans. In psychometric tests, volunteers recognized the supplementation of their body odour by MHC peptides and preferred ‘self’ to ‘non-self’ ligands when asked to decide whether the modified odour smelled ‘like themselves’ or ‘like their favourite perfume’. Functional magnetic resonance imaging indicated that ‘self’-peptides specifically activated a region in the right middle frontal cortex. Our results suggest that despite the absence of a vomeronasal organ, humans have the ability to detect and evaluate MHC peptides in body odour. This may provide a basis for the sensory evaluation of potential partners during human mate choice.